2020
DOI: 10.4102/phcfm.v12i1.2669
|View full text |Cite
|
Sign up to set email alerts
|

Incidental finding of COVID-19 infection amongst staff at a primary care facility in Ghana

Abstract: The COVID-19 pandemic has affected nearly every country worldwide and all African countries. The issue of healthcare workers (HCWs) contracting the disease is a growing concern in Ghana, because of the risk of spreading infections amongst themselves and to vulnerable patients in their care. This article illustrates how 14 staff at the Korle Bu Polyclinic/Family Medicine Department were incidentally found to be Covid-19 positive with most of them being asymptomatic. This observation led to a modification of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Majority of patients were asymptomatic in both groups, 29 (58%) in the first wave, and 36 (72%) in the second wave infections as shown in Table 1 . This finding is consistent with that recorded by Vandyke-Sey et al [ 21 ]. Both groups demonstrated a lack of symptoms in patients younger than 30 years old, and older than 79 years old.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Majority of patients were asymptomatic in both groups, 29 (58%) in the first wave, and 36 (72%) in the second wave infections as shown in Table 1 . This finding is consistent with that recorded by Vandyke-Sey et al [ 21 ]. Both groups demonstrated a lack of symptoms in patients younger than 30 years old, and older than 79 years old.…”
Section: Discussionsupporting
confidence: 94%
“…The gender distribution patterns are depicted in Figure 1 and show that for both groups there were more males than females. This contrasts the findings of Vandyke-Sey et al [ 21 ], but is consistent with updates from the Ghana Health Service [ 21 , 22 ]. The age of the study participants ranged from 14 to 84 years with a mean of 51.8 ± 15.6 years ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 87%
“…6 Sunanda Ray and Robert Mash services, to reduce the risk of infection and free up capacity to respond to the expected surge of patients with respiratory problems (Furstenburg et al, 2020;Mash, Goliath & Perez, 2020;Motlhatlhedi et al, 2020;Vandyck-Sey et al, 2020). A PHC facility readiness checklist was adapted from the National Institute for Communicable Diseases and used in Cape Town to assess the readiness of the PHC system across key inputs and service delivery domains.…”
Section: Internal Medicine Zimbabwementioning
confidence: 99%
“…Facilities attempted to comply with essential infection control methods: hand washing/sanitisation, physical distancing, use of face masks and other PPE as appropriate (Motlhatlhedi et al, 2020;Oseni et al, 2020;Vandyck-Sey et al, 2020). Most facilities attempted to separate patients into PUI with respiratory symptoms in a 'hot' stream and those without any symptoms into a 'cold' stream.…”
Section: Internal Medicine Zimbabwementioning
confidence: 99%
“… 4 Another study from Ghana found a high rate of COVID-19 among staff at a primary care clinic. 30 Although nosocomial transmission has been documented, no studies were found that evaluated the role of cohorting HCWs in reducing the risk of COVID-19 transmission.…”
Section: Questionsmentioning
confidence: 99%